Development of a product design system using a knowledge sorting process - Nyan Win Aung. (2008)
Knowledge sorting is one way to organize the knowledge acquired from the domain expert(s) and various sources. The development of a product design system is facilitated by the implementation of knowledge sorting process. The extraction of rule from knowledge becomes easier with the knowledge sorting process. Three phases based on relationships between attributes and factors, interrelationships between factors and relationships between dependent and independent variables are developed after the general sorting. The process is illustrated by applying it to the development of a product design system for helical compression springs.